Early Indian Palmistry: Śārdūlakarṇāvadāna: Pāṇilekhā - Zysk, Kenneth G. (History of Science in South Asia, 2025)
This paper offers a critical edition, translation, and notes to the chapter titled Pāṇilekhā or "the lines on the hands", from the Śārdūlakarṇāvadāna. It represents an early Indian formulation of palmistry that entered the texts in the latter half of the ninth century CE. It presents thirty-four verses in varying metres, suggesting compilation from diverse origins and dealing with omens and prognostication. Notably, it incorporates astrological elements, a feature not common in other early palmistry collections until much later. The paper includes critical remarks on the Sanskrit used and discusses different manuscript versions, aiming for an accurate representation of the original. Innovative is the use of more recent hand drawings in the understand of ancient text. Appendices provide translations of later palmistry texts like the Hastasañjīvana and Samudrikatilaka, along with historical illustrations of hand diagrams.